2023
DOI: 10.1002/jcp.30968
|View full text |Cite
|
Sign up to set email alerts
|

ADSCs‐exo attenuates hepatic ischemia–reperfusion injury after hepatectomy by inhibiting endoplasmic reticulum stress and inflammation

Abstract: Hepatic ischemia-reperfusion (I/R) injury commonly occurs during liver surgery.Exosomes from adipose-derived stem cells (ADSCs-exo) induce a hepatoprotective effect during hepatic I/R injury. This study aimed to investigate the possible mechanism by which ADSCs-exo attenuates hepatic I/R injury in rats. Rats were randomly divided into four groups: Sham, I30R + PH, ADSCs, and ADSCs-exo groups. Liver tissues were collected immediately after 24 h of reperfusion for further analyses. The content of inflammatory fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Meanwhile, VDR deficiency can deteriorate liver IR injury by disturbing M2 macrophage polarization. Previous research proved that VDR regulates inflammation through autophagy ( Lu et al, 2020 ; Fang et al, 2021 ) and M1/2 macrophage polarization ( Wang et al, 2017 ). We also found that the autophagy agonist RAP or inhibitor CQ could respectively enhance or weaken the role of VDR on M2 macrophage polarization in Figure 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, VDR deficiency can deteriorate liver IR injury by disturbing M2 macrophage polarization. Previous research proved that VDR regulates inflammation through autophagy ( Lu et al, 2020 ; Fang et al, 2021 ) and M1/2 macrophage polarization ( Wang et al, 2017 ). We also found that the autophagy agonist RAP or inhibitor CQ could respectively enhance or weaken the role of VDR on M2 macrophage polarization in Figure 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ADSCs can secrete a large number of cytokines to exert their effects. ADSCs can secrete cytokines such as IL-1α, IL-6, and IL-10 to play an anti-inflammatory role [ 13 ]. IL-1α binds to IL-1typeⅠreceptor and induces structural changes of IL-1R, interacts with IL-1RAcP, and initiates NF-κB signal transduction cascade [ 14 ].…”
Section: Adscs and Their Functionsmentioning
confidence: 99%
“…The EXs’ treatment significantly downregulated IL-6, interleukin-1β (IL-1β), and TNF-α levels and upregulated IL-10 levels. EXs displayed their hepatoprotective properties by preventing endoplasmic reticulum stress and inflammation [ 107 ].…”
Section: Studies Of Exs In Inflammatory Diseasesmentioning
confidence: 99%